The interaction between athletes attribution style, coping strategies and achievement motivation under failure situations - Chang, S.; Tang, T.; Ji, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: When athletes fail in competition, individual achievement motivation will be damaged. Studies show that attribution style and coping styles have an important regulating effect on improving the level of achievement motivation respectively. [1] Researchers have not found that the interaction between attribution styles and coping styles also has effect on it. By multiple correlational analysis of athletes` attribution style, coping way and achievement motivation under the failure situations, the research aimed to investigate the effect on achievement of the interaction between attribution style and coping styles. Methods Researchers adopt the CFDS [2], IDIAT[3] and Achievement Tendency Individual Diversity Questionnaire to implement retrospective surveys of 408 athletes. The attribution style was classified into 4 types — efforts, task difficulty, luck and abilities and is used as an independent variable. The coping way was classified into 4 types — problem-solving, seeking emotional support, avoiding and fantasy and helpless reaction was also used as an independent variable. The levels of achievement motivation were the dependant variables. The researchers analysed statistically, multiple correlation variables. Results The following correlations were found: When the athlete adopts efforts as attribution style and problem-solving as coping style, F=7.1. When the athlete adopts efforts as attribution style and avoiding and fantasy as coping style, F= 6.7. When the athlete adopts task difficulty as attribution style and problem-solving as coping style, F=6.18. When the athlete adopts task difficultly as attribution style and seeking emotional support as coping style, F=5.47. These combinations all show significant positive correlations. Conclusions Athletes` attribution style and coping strategy can interact and this interrelationship can affect the level of athletes` achievement motivation. When the athlete adopts efforts as attribution style and problemsolving as coping style, the interaction can promote the level of achievement motivation. Under these circumstances, the promotion effect is optimal. Therefore, after athletes fail in competition, the right way is to guide athletes to realize that a critical reason causing the failure is lack of enough effort. It is wise for athletes to face problems and solve problems. Therefore, the level of athletes` achievement motivation could be promoted and this offers psychological insurance to help athletes achieve excellent results.